(untitled) (Research, Society and Development, 2022)
Objective: To assess weight retention in adolescent mothers at the fourth postpartum month and its association with sociodemographic, reproductive, anthropometric and behavioral factors. Methods: Prospective longitudinal study. The survey was conducted in all public and private maternity hospitals in a city in the east of Minas Gerais State. All adolescent mothers (age <20 years) with childbirth at gestational age ≥37 weeks, without chronic disease, living in the municipality, whose delivery occurred between October/2018 and October/2019 participated. The first one took place 48-hours postpartum and the second, four months later. Four months postpartum the interview took place at the home of the mothers. Associations between variables were verified using Simple and Multiple Linear Regression. Results: Of the 367 interviewed adolescent mothers at the maternity hospitals, the predominant characteristics were age between 18-19 years, non-white skin color and education above nine years of study. Four months postpartum, 317 mothers were evaluated and the incidence of weight retention was 79.4% (n=247) with an average of 6.86 kg ±5.34. Higher means of weight retention were observed in mothers with less school years, greater number of children, higher daily consumption of ultra-processed food during pregnancy, without nutritional guidance during pregnancy, higher pre-gestational Body Mass Index and greater gestational weight gain (p<0.05). Conclusions: The incidence of weight retention was considered high, a fact that highlights the importance of prenatal care quality, including nutritional education strategies, especially for this age group, highly vulnerable.